The Enterprise 2.0 concept: challenges on data and information security - Silva, Ana (2018)
The Web 2.0 wave has “hit” businesses all over the world, with companies taking advantage of the 2.0 concept and new applications stimulating collaboration between employees, and also with external partners (suppliers, contractors, universities, R&D organizations and others). However, the use of Web 2.0 applications inside organizations has created additional security challenges, especially regarding data and information security. Companies need to be aware of these risks when deploying the 2.0 concept and take a proactive approach on security. In this paper are identified and discussed some of the challenges and risks of the use of Web 2.0 tools, namely when it comes to securing companies’ intellectual property.